Unplanned hospital readmissions following congenital heart diseases surgery: Prevalence and predictors - Azhar, Ahmad S. (Saudi Med J, 2019)
OBJECTIVES: To estimate the rate of unplanned hospital readmission following surgical repair of congenital heart defects (CHD) and investigate the related causes and risk factors. METHODS: A retrospective chart review of all the patients who underwent surgical repair of CHD at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. The study outcome consisted of any hospital admission during the 12 months following the first reparative surgery. Exclusion criteria included planned admissions. Patients’ demographic and readmission data as well as the perioperative data were collected and analyzed as factors and predictors of unplanned readmission RESULTS: After the exclusion of the deceased patients, a total of 189 patients were included. The readmission rate was 15.9% during a one-year period following surgery. There was a significant association between the probability of readmission and preoperative mechanical ventilation (MV) (p<0.001), intraoperative complications (p=0.025), prolonged postoperative length of stay (LOS) (p<0.001), early postoperative complication (p=0.007), long postoperative MV stay, and drain tube stay (p=0.011). Significant predictors of unplanned readmission included young age (1-12 months) and low weight at surgery (<5kg), preoperative MV, intraoperative complications, postoperative LOS ≥10 days, pediatric intensive care unit stay, MV stay, drain tube stay, infections, respiratory complication, and feeding problems. Only the preoperative MV and LOS >10 days were the independent risk factors. CONCLUSION: Readmission rates were similar to those reported in other studies. Future studies are warranted to investigate suitable actions to alleviate the modifiable risk factors, such as postoperative complications.